EFEKTIVITAS PERANGKAT PEMBELAJARAN TOULMIN ARGUMENTATION PATTERN (TAP) BERBASIS MODEL ADI DAN EKSPERIMEN UNTUK MELATIH KETERAMPILAN ARGUMENTASI ILMIAHASED ON THE ADI MODEL AND EXPERIMENTS FOR TRAINING SCIENTIFIC ARGUMENTATION SKILLS - Marsi'ah, Siti; Rakhmawan, Aditya; Ahied, Mochammad; Hadi, Wiwin Puspita; Yamin, Yamin (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2024)
This research aims to determine the effectiveness of the Toulmin Argumentation Pattern (TAP) based on the ADI model and experiments in training scientific argumentation skills. Learning tools include teaching modules, LKPD, infographics and scientific argumentation tests. The development of learning tools uses a 4D development model, which consists of Define, Design, Develop and Disseminate, but in the implementation of this research it only focuses on validation testing at the disseminate stage. The research sample included 15 students in class VIII C at UPTD SMPN 1 Sepulu, who were selected using a purposive sampling technique. Data collection techniques use questionnaires, interviews, observation and documentation. Based on the research results, it was found that the learning tools developed had an average validity of each for the teaching module, namely 95%, LKPD 93%, infographics 92%, scientific argumentation test 92% with very feasible criteria and reliability respectively, namely the teaching module 96 %, LKPD 96%, infographics 96%, and scientific argumentation test questions 95% with very reliable criteria. The results of the N-Gain Score for students' scientific argumentation were 0.7 with high criteria. Average readability is 99% with very readable criteria. The average student response was 92% with very good criteria